Energy-Saving Solutions Applied in Belt Conveyors: A Literature Review - Martyna Konieczna-Fuławka (Energies)
Belt conveyors are essential systems for the continuous transport of various materials across many industries, particularly in bulk material handling for mining. While they are often the most economical solution, they still consume a significant amount of energy. This article discusses the latest advancements and the current state of energy-saving solutions for belt conveyors. Key solutions include low-friction belts, variable-frequency drives (VFDs), monitoring systems, automation, and regenerative belt conveyors. It is important to note that selecting the right construction parameters, performing preventive maintenance, and using appropriate materials are crucial for reducing energy consumption. By combining these energy-saving technologies with well-chosen construction parameters, it is possible to develop sustainable belt conveyors.